Managing commodity booms--and busts - Varangis, Panayotis N.; Akiyama, T. (Takamasa), 1944-; Mitchell, Donald O. (Washington, D.C. : World Bank, 1995)
Why booms happen -- Why this boom won't continue -- Managing booms and busts -- Learning from experience -- Who manages the boom? -- How to manage booms.
Includes bibliographical references (p. 21-22).
oif 12/08/15
Loan
Keywords: Commodity futures -- Developing countries; Primary commodities -- Prices -- Developing countries -- Forecasting; Export marketing -- Government policy -- Developing countries